Sistema de control aplicado a los procesos administrativos y su influencia en la imagen institucional de la empresa “BLUECORP S.A EDS COLOMA - Núñez Meléndez, Solange Catherine (2017)
ince the beginning of remote times, the human being has been in need of controlling their properties and those of the whole of which is part, since previously existed and used rustic control models to avoid embezzlement, due to such situation, it is necessary that every company establishes a control system, since this improves the financial, administrative and legal situation of the companies